Analysis of Cooling Load in Room GK1-103, Institut Teknologi Sumatera - Mohd Zailani, Muhamad Iman Bin; Ahmad Zamri, Nur Alia Batrisyia Binti; Rajagukguk, Gabriel Xaverius Englando; Hafidz, Mochammad Januar; Wahyudi, Aldrian; Sitinjak, Jerniko; Silitonga, Dicky J. (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
The cooling load, which refers to the amount of heat energy that must be removed to maintain a comfortable indoor environment, is affected by various factors such as external temperature, building design, occupancy levels, and internal heat sources. Accurate cooling load calculations help engineers and designers create systems that meet comfort demands without excessive energy consumption, aligning with ITERA's goals for sustainable development and environmental responsibility.